PENGARUH TEKNIK PIJAT OKSITOSIN TERHADAP PENURUNAN NYERI PERSALINAN : EVIDENCE BASED CASE REPORT (EBCR) (Jurnal Kesehatan Siliwangi, 2022)
Background: Labor pain is a factor that can cause discomfort and anxiety. This can result in weak uterine contractions so that prolonged labor will occur. One effort to deal with labor pain can be done with pharmacological and non-pharmacological methods. One of the non-pharmacological methods is by using oxytocin massage. Purpose: This evidence-based case report aims to determine whether oxytocin massage can reduce labor pain in the first stage of labor at the Pacet Health Center, Bandung Regency. Method: Search for articles about the effectiveness of oxytocin massage in labor mothers was conducted on Garuda and Google Scholar. The keywords used were "effect", "oxytocin massage", and ", "labor pain". Article searches were limited by inclusion criteria, namely articles that published within the last 5 years, in the form of full text articles, and according to clinical questions.Results: How many articles were found, namely 3 research articles using the Quasi-experimental method by Merry Wijaya, et al, Laily Himawati, et al, and Umu qonitun, et al. which met the inclusion criteria and were filtered and then analyzed critically. Based on the two journals, they both show evidence that oxytocin massage has an effect on reducing active phase I labor pain. After critically reviewing the research, it was found to be valid, important, and applicable to patients. Conclusion: : Oxytocin massage is one of the applications of non-pharmacological techniques that can show effectiveness in reducing active phase I labor pain.